TOGAF-Based Business Architecture Design in Digital Advertising Photography Services - Handono Warih; Richardus Eko Indrajit; Erick Dzaki (Poltanesa, 2025)
Digital transformation in the creative industry drives the need for structured business architecture to support advertising photography services. This study examines the application of Enterprise Architecture using the TOGAF framework in companies that provide digital photography and advertising services. A case study was conducted on the Pointin. AI service, which offers project-based photography solutions, content subscriptions, integrated visual advertising, and AI-based retouching services. Using the TOGAF ADM approach and the ArchiMate model, this study maps business processes, applications, and strategic capabilities to achieve higher operational efficiency and technology integration. The results show that the enterprise architecture approach provides clarity, alignment between teams, and supports data-driven decision making.